Efforts to Increase Sales During the Covid-19 Pandemic at Alta Cake & Pastry - Nathasya Benska, Vicka; Ariyo Bimo, Widhi (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2023)
The Alta Cake & Pastry as a business partner that introduces products to the market relies on manual product sales by word of mouth who place orders for their products, open a small shop that is integrated with the owner's house, and online marketing through social media. And Alta Cake & Pastry business can be categorized into Small and Medium Enterprises (SMEs). This study aims to find out how marketing efforts can increase sales at the Alta Cake & Pastry business during the Covid-19 pandemic situation. The research was conducted using a descriptive method, where data were obtained using an observational approach through direct interviews with the owner of the Alta Cake & Pastry shop. The results of the research from the Alta Cake & Pastry business use 4 (four) strategies, namely production strategy, price strategy, promotion strategy, and distribution strategy. With this KKNGTM activity, it is hoped that the Alta Cake & Pastry business can further develop the strategies that were previously used.